Atopic Dermatitis and Canadian Indigenous Peoples: Burdens, Barriers, and Potential for Solutions (Canadian Allergy & Immunology Today, 2022)
Atopic dermatitis (AD) is the most common chronic inflammatory skin disease worldwide. AD begins before age five in 90% of cases and is associated with the development of comorbid conditions such as infections, environmental allergies, food allergies, asthma, anxiety/depression, and abnormalities in sleep, growth, and development. While personal experience suggests that Canadian Indigenous peoples, including children and youth, are facing burdens associated with AD, formal research studies addressing the impact of AD and skin disease in general on Canadian Indigenous peoples are lacking. Canadian Indigenous* account for approximately 5% of the Canadian population. Although Canadian Indigenous vary widely in geography, culture, language, and beliefs, they face common health disparities embedded in complex historical and social contexts related to factors such as colonization, intergenerational trauma from residential schools and institutionalization, racial segregation in the form of reservations, systemic racism, and being subjected to policies such as the ‘Indian Act’. This article reviews the burdens and barriers of AD in Canadian Indigenous by examining the literature, experiences of health care practitioners (HCPs), and media reports followed by proposing potential solutions to address such disparities.